Pengaruh Modal Usaha, Lokasi Usaha, Biaya Produksi dan Jumlah Tenaga Kerja Terhadap Tingkat Pendapatan UMKM dalam Sektor Kuliner di Kota Gorontalo - Moh Alif Rifqhi; Irawati Abdul; Sri Indriyani S. Dai (Economic Reviews Journal, 2025)
The research findings indicate that business capital contributes 23.4% to MSME income, but its impact is not significant. Business location contributes 14.3%, which is also not significant in affecting MSME income. On the other hand, production costs have a negative impact of -72.3%, indicating that high production costs can reduce income, although the result is not significant. Conversely, the number of workers significantly contributes 31.7%, emphasizing that good labor management can significantly increase MSME income. Overall, the independent variables in this study explain 30.8% of the variation in MSME income, while the remaining 69.2% is influenced by factors outside the model. These findings underscore the importance of optimizing labor management and improving production cost efficiency to support income growth for culinary MSMEs in Gorontalo City.